Life table of the predator Alloeocranum biannulipes Montrouzier and Signoret (Hemiptera: Reduviidae) and a test of its ability to suppress populations of Dinoderus porcellus Lesne (Coleoptera: Bostrichidae) in stored yam chips - Loko, Y.L.E.; Gavoedo, D.M.; Toffa, J.; Orobiyi, A.; Thomas-Odjo, A.A.; Tamò, Manuele (Elsevier, 2019)
Stored yam chips are attacked by Dinoderus porcellus Lesne, which can cause significant losses. The predator Alloeocranum biannulipes Montr. and Sign. is a potential biological control agent of D. porcellus. The biology, predation and mating behaviour of A. biannulipes were investigated under laboratory conditions. Moreover, the regulatory effect of this predator on population dynamics of D. porcellus, and hence on yam chips losses, were evaluated under both laboratory and natural conditions. Female A. biannulipes laid on average 42.1 ± 6.8 eggs, which hatched some 4.3 ± 0.3 d after laying, with a hatching rate of 86%. A total of five nymphal stages were recorded with a total nymphal period of 28.2 ± 0.1 d, and a total developmental period of 32.4 ± 2.3 d. Female A. biannulipes lived longer (29.3 ± 1.3 d) than did the males (25.8 ± 4.1 d). Periods of pre-oviposition, oviposition, and post-oviposition were 12.8 ± 1.7, 10.5 ± 1.0 and 5.3 ± 0.5 d, respectively. Life‐table analysis revealed an intrinsic rate of increase 0.29 females/day and a gross reproductive rate of 28.38 females/female. The predator A. biannulipes exhibited a ‘pin and jab’ mode of predation, and its mating behaviour consisted in sequential actions (excitation and approach, riding over, copulation and post-copulation). Under laboratory conditions, A. biannulipes significantly reduced the numbers of D. porcellus and the weight loss of yam chips after 8 weeks at the initial density of 10 predator for 20 preys. Similar trends were observed under farmer storage conditions; there was a significant reduction in the D. porcellus population and in weight loss of yam chips as compared to the control treatment after 8 and 12 weeks for all tested density prey/predator. Therefore, our findings showed that A. biannulipes can be mass reared under laboratory conditions and has the potential to be an effective biological agent against D. porcellus in stored yam chips.